2021
DOI: 10.3389/fphar.2021.709467
|View full text |Cite
|
Sign up to set email alerts
|

Elabela Protects Spontaneously Hypertensive Rats From Hypertension and Cardiorenal Dysfunctions Exacerbated by Dietary High-Salt Intake

Abstract: Objectives: Arterial hypertension, when exacerbated by excessive dietary salt intake, worsens the morbidity and mortality rates associated with cardiovascular and renal diseases. Stimulation of the apelinergic system appears to protect against several circulatory system diseases, but it remains unknown if such beneficial effects are conserved in severe hypertension. Therefore, we aimed at determining whether continuous infusion of apelinergic ligands (i.e., Apelin-13 and Elabela) exerted cardiorenal protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 100 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…ELA, a novel endogenous molecule, is predominantly expressed in the kidney, heart, blood vessels, and other tissues [ 24 ] . It has been identified to play important roles in various organisms and has the potential to alleviate cardiac and renal remodeling [ 25 26 , 31 ] . Previous studies showed the possibility that ELA might exert beneficial effects on ischemia-reperfusion renal injury recovery [ 28 ] .…”
Section: Discussionmentioning
confidence: 99%
“…ELA, a novel endogenous molecule, is predominantly expressed in the kidney, heart, blood vessels, and other tissues [ 24 ] . It has been identified to play important roles in various organisms and has the potential to alleviate cardiac and renal remodeling [ 25 26 , 31 ] . Previous studies showed the possibility that ELA might exert beneficial effects on ischemia-reperfusion renal injury recovery [ 28 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, apelin/ELA and AngII exerted an opposite effect on vessels. In this regard, it has been reported that administration of either apelin or ELA had a blood pressure-lowering effect, potentially indicating a therapeutic role of these peptides in reverting hypertension, thus reducing the risk of developing HF [ 67 , 68 ]. In addition, apelin is capable of boosting ACE2 expression, and this is another mechanism by which it counteracts RAS.…”
Section: Cardioprotective Role Of Apj Endogenous Ligandsmentioning
confidence: 99%
“…In line with the in vitro results, apelin KO mice also showed downregulation of ACE2 expression and, consequently, low ACE2 protein level [ 69 , 70 ]. Of note, ACE2, which primarily acts on AngiII, has a role in apelin metabolism because it can cleave apelin into inactive isoforms, though it is unable to degrade ELA [ 23 , 66 , 67 ]. Conversely, ELA did not affect ACE2 expression, but it reduced angiotensin-induced blood pressure via downregulation of ACE expression.…”
Section: Cardioprotective Role Of Apj Endogenous Ligandsmentioning
confidence: 99%
“…Additionally, the apelinergic system (composed of apelin and elabela as well as APJ receptors) is believed to be a promising target for the treatment of cardiovascular disease. Both apelin and elabela possess inodilator properties ( Sainsily et al, 2021 ). However, the effects of sacubitril/valsartan on apelin and elabela have not been studied.…”
Section: Effects Of Sacubitril/valsartan On Renin-angiotensin-aldoste...mentioning
confidence: 99%